Community-based Social Protection for the Elderly in Werdha Coral Bimo Seno Cartoharjo Township Madiun - Niam, Muh Niam; Utami, Istiqomah Bekhti; Daliman, Daliman; Sarmono, Sarmono; Dewantara, Setiya (Universitas Muhammadiyah Surakarta, 2023)
The elderly life stage is a stage of life that has risks in various aspects of life, however, elderly people still have the desire to maintain their independence and dignity in social life. Therefore, care and protection for the elderly must also pay attention to the social environmental conditions of the elderly's life. Social protection in the form of social assistance and social security for the elderly needs to continue to be improved so that it can bring benefits that can be felt directly by the elderly. This research was conducted using a qualitative descriptive approach, which aims to describe community-based social protection for the elderly through Karang Werdha Bimo Seno, Kartoharjo Village, Madiun City. The research results show that Karang Werdha Bimo Seno is a Geographical Community and a Functional Community and is an organization that emerged on the initiative of the community and stakeholders in Kartoharjo Village. Karang Werdha Bimo Seno's activities in providing social protection for the elderly include direct services such as; Elderly sports activities and health services for the elderly, as well as financial assistance provided every two weeks to the elderly in turn, can help overcome the vulnerability of the elderly. Indirect social protection for the elderly (indirect services), namely through health services with five Posyandu in Kartoharjo Village, assistance for the elderly with Wahana Kesejahteraan Sosial Berbasis Masyarakat (WKSBM), as well as various assistance and services for the elderly from both the regional and central government. Community-based social protection for the elderly implemented by Karang Werdha Bimo Seno in the form of direct services and indirect services in Kartoharjo Village, Madiun City contributes to supporting the lives of the elderly in their community environment.